Golden fruit a cultural history of oranges in Italy - Mazzoni, Cristina 1965- (Toronto Italian studies, 2018)
Through close readings of key texts, including spiritual writings, fairy tales, and a botanical treatise, Golden Fruit examines the role of oranges in Italian culture from their introduction during the medieval period through to the present day